Are We on the Same Page? A Multi-Institutional Evaluation of Faculty and Resident Training Needs. (October 2017) - Braun, Kelli; Swift, Steven; Beasley, Anitra; Wyatt, Tasha; Toomey, Mitchell; Stepleman, Lara
Abstract : BACKGROUND: Resident and faculty needs are important in guiding the educational agenda; studies demonstrate that these groups do not always agree on needs. A previously piloted 50-item needs assessment evaluating content areas of feedback, the 15 Ob-Gyn milestone procedures, and simulation was used to assess and compare faculty and resident needs. METHODS: The needs assessment was administered electronically to two academic Ob-Gyn residency programs (located in South Carolina and Texas) in June 2016; all items were ranked on a 5-point agreement scale. Equivalent versions were written to capture resident and faculty perceptions of the training program; results were anonymous and participation was voluntary. RESULTS: Forty-two surgical faculty (52.5%) and 47 residents (62.5%) completed the needs assessment; t tests compared resident/faculty group differences. Both groups agreed on the adequacy of surgical content, however, faculty consistently self-reported delivering feedback at a significantly higher level than residents' perceived receiving it ( P <.05) for 8/16 feedback items. Overall, both groups were least satisfied with training in breech vaginal delivery, 3rd/4th-degree laceration repair and operative vaginal delivery; residents were most satisfied with training in cesarean delivery while faculty were most satisfied with laparoscopy. Both groups agreed simulation can improve procedure performance; no significant differences existed. These findings were consistent between institutions, although each institution's levels of agreement differed for individual items. DISCUSSION: Although residents and faculty agree on areas of strengths and weaknesses, significant differences exist in perception of feedback delivery and reception.